CHALLENGES AND PROSPECTS FOR BIOETHICS FORMATION FOR STUDENTS IN THE BUSINESS AREA - Gutiérrez Huby de Segura, Ana María (2014)
This article addresses in bioethics from an educatio-nal context. The need to incorporate it as an applied discipline within enterprise education, to guide the establishment of principles and the approach to situa-tions involving human life is posed. Among the topics covered are concepts and principles of bioethics and its relationship with business functions, the state’s role as guarantor of citizen education law and building a just and humane society, reasons why include it as a discipline in university curriculum, develop compe-tencies in students aspects comprising the training of trainers, methods and strategies for curriculum design, challenges and perspectives presented for training in bioethics. He reached the following conclusions: At the institutional level there is no consistency in the mission to develop bioethical profile students. The curricula of business area do not include bioethics in the curriculum; therefore, a low level of understanding of this concept is reflected in students.